Sickle Cell Anaemia: Knowledge And Attitude Toward The Disease Among The Population In West Libya - Madour, Ali; Mawada Abduljalil; Sarah Abduljalil; Khawla Altam; Eanas Elmaihub (AlQalam Journal of Medical and Applied Sciences, 2025)
Sickle Cell Disease (SCD) is one of the most common hereditary disorders worldwide, with variable prevalence across Libya. While high rates are observed in the Marzouk and Taourga populations, most other regions report lower incidence. Existing literature underscores the urgent need for improved public education and awareness regarding SCD. This study assessed the level of SCD awareness among college students, healthcare workers, and the general population in western Libya, aiming to identify gaps and inform future awareness programs. A cross-sectional questionnaire-based survey was conducted among healthcare workers, medical students, and the public. The instrument, prepared in English and translated into Arabic, was distributed both electronically (Google Forms) and in printed form. It comprised 15 items assessing SCD knowledge and awareness. Data were summarised as frequencies and percentages, and associations were evaluated using the Chi-square test. Of 999 respondents, 739 (74%) had heard of SCD, with the highest proportion among healthcare workers (46%), followed by college students (40%) and the general public (13%). The most common source of information was college education (349; 47.2%). Awareness was significantly higher among females (78%) than males (65%), with females demonstrating greater overall knowledge. Awareness of SCD in western Libya is moderate overall, with notable differences by gender and occupation. Healthcare workers and college students exhibited both higher knowledge levels and healthier attitudes toward preventive behaviours, including marriage decisions. These findings highlight the need for targeted educational campaigns, integrating SCD into broader health education initiatives to enhance public understanding and preventive practices.